1997
DOI: 10.1097/00007890-199708270-00008
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus (Fk506) Down-Regulates Free Radical Tissue Levels, Serum Cytokines, and Neutrophil Infiltration After Severe Liver Ischemia

Abstract: These data indicate a new and different protective mechanism for FK506 in regard to its ability to down-regulate free radical levels in livers subjected to severe ischemia and reperfusion. Tacrolimus, also confirmed to be a potent suppressor of the cytokine response, specifically interleukin 1 and tumor necrosis, decreased neutrophil tissue migration as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
7

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 17 publications
2
41
0
7
Order By: Relevance
“…[23][24][25] More recently, it was documented to reduce expression of adhesion molecules, with a demonstrated reduction in leukocyte rolling and adhesion. 19 In conclusion, although complete elucidation of the role of tacrolimus in hepatic I/R injury deserves further investigation, in this trial, the first prospective randomized trial conducted in the clinical arena, we show that use of a flush solution containing tacrolimus results in superior early graft function and decreased hepatocellular injury.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…[23][24][25] More recently, it was documented to reduce expression of adhesion molecules, with a demonstrated reduction in leukocyte rolling and adhesion. 19 In conclusion, although complete elucidation of the role of tacrolimus in hepatic I/R injury deserves further investigation, in this trial, the first prospective randomized trial conducted in the clinical arena, we show that use of a flush solution containing tacrolimus results in superior early graft function and decreased hepatocellular injury.…”
Section: Discussionmentioning
confidence: 56%
“…11,18 Some investigators have suggested that neutrophil infiltration and cumulative free radical release are the most important mediators of I/R injury. 19,20 Tacrolimus, as an immunomodulatory agent, is likely to have a profound effect on the inflammation avenue of I/R injury. It has been shown to block early activation of the transcription factor nuclear factor-B.…”
Section: Discussionmentioning
confidence: 99%
“…43 Several investigators have documented decreased free radical production in association with amelioration of I-R injury when tacrolimus is administered before ischemia. [44][45][46] Although these studies document an end result of tacrolimus pretreatment as suppression of free radical elaboration, they offer little insight to the mechanisms responsible for such effects. Maintenance of cellular ATP content, suppressed free radical elaboration, and possible antioxidant activities are all possible mechanisms acting to produce tacrolimus-induced free radical protection.…”
Section: Free Radical-mediated Injurymentioning
confidence: 99%
“…107 Although not specifically studied, this mechanism is a possible means for tacrolimus to inhibit apoptosis, being a well-documented inhibitor of TNF-␣. 44,[71][72][73][74] Inhibition of calcineurin-mediated dephosphorylation of NOS causes decreased NOS activity. 107 Recent studies in a cancer model have shown inducible NOS activity to correlate directly with apoptosis.…”
Section: Apoptosis Versus Necrosismentioning
confidence: 99%
“…Increased levels of ROS are known to be involved in the pathogenesis of IRI. The application of FK506 (tacrolimus) in vivo is associated with a reduction of ROS (29). FK506 (tacrolimus) has also been found to exert anti-apoptotic effects by preventing Fas-induced apoptosis in human hepatocytes in vitro (33), as well as in an in vivo model of IRI in rats (34).…”
Section: Discussionmentioning
confidence: 99%